Pengendalian Persediaan Sparepart dengan Menggunakan Metode Fifo di Warehouse di PT.Heinz ABC Indonesia Pasuruan - Muhammad Lazuardi Ramadhan; Ayik Pusakaningwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Spare parts inventory is a common problem faced by many companies that use lots of machines or robots in their production processes. Where the spare parts warehouse in the company is required to always be prepared and there is no delay in the availability of spare parts to continue to support production machine activities. If the availability of spare parts is late or empty, it will hamper the production process activities within the company. Seeing this problem, researchers are trying to maintain the availability of spare parts using the FIFO (first in first out) method so as to prevent delays or stock shortages. The FIFO method is a method of inventory management that uses product stock in the warehouse based on the time of entry. By using this method, it is hoped that there will be no delays or stock vacancies in the warehouse due to irregularities in picking up spare parts in the warehouse. The aim of this research is to ascertain how the use of the FIFO method affects the warehouse's ability to manage spare parts inventory efficiently. Field research is this type of research. This research uses a qualitative data analysis methodology and inductive reasoning, which starts with precise and real facts before drawing conclusions from them. The research results provide significant benefits in increasing operational efficiency and reducing the possibility of excess or shortage of stock, which can disrupt production and delivery processes. Efficient receiving also helps in maintaining spare parts quality, ensuring that only items that meet quality standards are received and stored. Application of the FIFO method in the spare parts warehouse at PT. Heinz ABC Indonesia also has a positive impact on inventory recording and reporting. With a more regular flow of goods in and out, the recording system becomes more accurate and easier to track. This makes it easier for the accounting and management team to carry out audits and identify potential problems.